Sporicidal properties of a composite nanomaterial based on silver and copper nanoparticles and chlorhexidine against the anthrax pathogen - S. V. Derevianko; V. I. Bolotin; V. V. Ukhovskyi; V. L. Arefiev; N. R. Demchenko; M. Y. Romanko; V. H. Kaplunenko; A. M. Demchenko (Regulatory Mechanisms in Biosystems, 2026)
The s earch for new substances with bactericidal and sporicidal properties and the development of modern antimicrobial preparations and disinfectants is one of the most important tasks in microbiology. In this work the sporicidal properties of nanoparticles (NPs) and composite nanomaterials (NMs) against the Bacillus anthracis strain "SB" were studied. The sporicidal properties of chelated Zn NPs, Se/I NPs, NMs based on Ag/Cu NPs, CHH, and NMs based on Ag/Cu NPs combined with CHH were studied at concentrations ranging from 0.0125 to 250 mg/cm³ and exposure times of 2, 6, 12, and 24 hours using spores of B. anthracis strain "SB". Viability of spores was assessed on Petri dishes with tryptic soy agar. Colony counting was performed after 24 hours of inc u bation at 37 ± 0.5 °C. It was established that upon contact of B. anthracis "SB" strain spores with CHH at a co n centration of 380 µg/cm³ for 2 hours, high statistically significant sporicidal activity (100 %) was observed. At a concentration of 38 µg/cm³, CHH caused a significant reduc tion in spore viability by 89.9 %. High sporicidal activity was exhibited by Ag/Cu NPs at concentrations of 250 and 25 µg/cm³ of each element, causing statistica l ly significant spore inactivation of 100% and 78.9%, respectively. At a concentration of 2.5 µg/cm³, a significant reduction in spore viability by 19.7% was observed. NMs based on Ag/Cu NPs and CHH at concentrations of 125, 125, and 190 µg/cm³ of each composite respectively, caused 100% loss of spore viability of the B. anthracis "SB" strain. With a combination of particles at a concentration of 1.25 µg/cm³ (Ag), 1.25 µg/cm³ (Cu), 1.90 µg/cm³ (CHH), the spore titer was significantly reduced by 56.4%. On tryptic soy medium, the B. anthracis "SB" strain forms opaque white colonies with irregular edges, 2–3 mm in size. No changes in colony morphology were observed under the action of CHH. Upon contact with NMs based on Ag/Cu NPs and NMs based on Ag/Cu NPs combined with CHH, a 2–4-fold reduction in colony size compared to the control was observed. Thus, all tested substances demonstrated high sporicidal activity. The highest sporicidal activity was shown by NMs based on Ag/Cu NPs combined with CHH. The influence of the above-mentioned NMs on colony morphology was noted. These investigated NMs can be used for the development of methods for soil sanitation and decontamination of environmental objects, as well as for the development of antimicrobial agents against the anthrax pathogen.